Meningkatkan Hasil Belajar Peserta Didik dengan Model Pembelajaran Kooperatif Berbantuan Flashcard Materi Klasifikasi Makhluk Hidup - Salbiah, Salbiah; Titin, Titin; Wahyuni, Eko Sri; Ningsih, Kurnia; Yuniarti, Anisyah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to improve the learning outcomes of seventh-grade students in class VII A at SMPN 22 Pontianak on living organisms' classification through a cooperative learning model assisted by flashcards. The Classroom Action Research (CAR) model has two cycles, each including four stages: planning, implementation, observation, and reflection. Data collection methods involved the learning outcome tests, observation sheets, and documentation. This research focused on analyzing changes in students' understanding of active and interactive learning strategies using flashcards. The results showed a significant improvement in student learning outcomes; the mastery level was 81.25% in the first cycle, which increased to 87.50% in the second cycle. This increase indicates that the cooperative learning model assisted by flashcards not only enhances student engagement in the teaching-learning process but also effectively strengthens their understanding of the material on the classification of living organisms. The findings suggest that integrating cooperative methods with visual aids, like flashcards, can be an effective pedagogical strategy to enhance the quality of education in schools.